2015
DOI: 10.1016/j.rdc.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Polyarteritis Nodosa

Abstract: Polyarteritis nodosa (PAN) is a systemic disease, but variants are cutaneous PAN and single-organ disease. Histologic confirmation of vasculitis in medium-sized arteries is desirable, and biopsies should be obtained from the symptomatic and least invasive sites. Angiography can show multiple microaneurysms in the viscera. Treatment includes high-dose corticosteroids, which are combined with immunosuppressive agents when internal organs are involved and with life-threatening disease. Once remission is achieved,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 50 publications
1
32
1
Order By: Relevance
“…The male/female (M/F) ratio was 0.5 in children while there was a clear male predominance in adults (M/F 4.5). The median age at disease onset was 11 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) in children and 33 (19-71) years in adults. Nineteen adult patients (86.4%) also fulfilled the Ankara 2008 criteria for PAN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The male/female (M/F) ratio was 0.5 in children while there was a clear male predominance in adults (M/F 4.5). The median age at disease onset was 11 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) in children and 33 (19-71) years in adults. Nineteen adult patients (86.4%) also fulfilled the Ankara 2008 criteria for PAN.…”
Section: Resultsmentioning
confidence: 99%
“…4 The peripheral nervous system and the skin are the most commonly involved sites 4 while it has a striking tendency to spare the lungs in contrast to the ANCA-associated vasculitis. 5 We lack studies comparing the characteristics of pediatric-and adult-onset PAN. Hence, our study aims to investigate the differences in clinical parameters, laboratory data, treatment and outcomes between adult-and childhood-onset PAN.…”
Section: Introductionmentioning
confidence: 99%
“…PAN typically affects skin, joints, peripheral nervous system, digestive tract and kidneys [2]. Here we present a case of PAN with extremely severe combined kidney damage.…”
Section: Introductionmentioning
confidence: 93%
“…In 2014 Zhou et al 27 and Navon-Elkan et al 28 identified biallelic loss-of-function CECR1 mutations in patients presenting with fevers and early-onset strokes and/or with vasculitis resembling polyarteritis nodosa (PAN), a systemic necrotizing vasculitis typically affecting medium-sized muscular arteries 29 . Zhou and her colleagues reported nine patients with fevers, early-onset (< 5 years old) lacunar strokes, livedoid rash, hepatosplenomegaly, cytopenia, and systemic vasculopathy, including two patients with PAN and one with small-vessel vasculitis.…”
Section: Deficiency Of Ada2 (Dada2)mentioning
confidence: 99%